Redesigning River des Peres: to improve, protect, and maintain - Denney, Anne (Kansas State University, 2013)
During a 75-year building boom starting in the early to mid 1900's we built most of the stormwater and sewage infrastructure that sustains us today. As these infrastructural systems begin to meet their life expectancy, and with our cities being impacted by flooding, rapid urbanization, and water quality concerns there is a need for designers to begin rethinking these infrastructural systems. With rapid urbanization cities are seeing increased peak flow discharge volumes within their river systems and combined sewer overflow occurrences. The River des Peres located in the City and County of Saint Louis, Missouri, is an urban waterway that is affecting the natural ecosystem and community well-being. The main stem of the River des Peres is a heavily degraded concrete trapezoidal channel that in 1988 became a National Historic Civil Engineering landmark for its sewerage and drainage works. Which leads to the question of why a historic civil engineering landmark, such as the River des Peres, is such a wreck today? In compliance with the Clean Water Act the Metropolitan St. Louis Sewer District is proposing to implement enhanced green infrastructure and stormwater/sewer storage tanks to reduce the amount of Combined Sewer Overflow (CSO) occurrences in the River des Peres watershed. However, through review of literature, site inventory and analysis, a watershed stormwater BMP plan, and corresponding site design developments it has been found that return frequency flow can be reduced as much as 56% in the watershed, reducing the need for storage tanks and reducing CSO occurrences. Through the incorporation of stormwater best management practices (BMPs) the River des Peres responds to recurrence flow, wildlife habitat, and to the well-being of the community.
Keywords: River des Peres; Bankfull discharge; Urban ecology; Green infrastructure; Biodiversity; Water quality; Landscape Architecture (0390); Urban Planning (0999); Water Resource Management (0595)